Characterization of Prussian blue-immobilized chitin-coated nylon fibers as adsorbent for cesium ions - Dechojarassri, Duangkamol; Omote, Sahori; Minamino, Takanori; Nishida, Kensuke; Furuike, Tetsuya; Tamura, Hiroshi (Engineering and Applied Science Research, 2018)
A Prussian blue (PB; KFe)-immobilized chitin-coated nylon (KFe/CT/nylon) fiber was successfully synthesized for the first time. The characteristics of this fiber were compared to that of a KFe-immobilized chitosan-coated rayon (KFe/CTS/rayon) fiber, which shows excellent cesium ion (Cs+) adsorption and has a high potential for practical use. The aim of producing the KFe/CT/nylon fiber is to study the feasibility of using it instead of a KFe/CTS/rayon fiber to adsorb Cs+ from contaminated water. CT can not only react with KFe but is also cheaper than CTS; therefore, it is interesting to consider KFe/CT/nylon fiber as an alternative material for Cs+ adsorption. The interactions between KFe and CT in the nylon fiber or KFe and CTS in the rayon fiber were confirmed via X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), and Fourier transform infrared (FTIR) spectroscopy. The Cs+ concentration was determined using inductively coupled plasma mass spectrometry (ICP-MS). The Cs+ adsorption capacity of the KFe/CTS/rayon and KFe/CT/nylon fibers were compared. The Cs+ adsorption capacity of the KFe/CTS/rayon fiber (90.5%) was found to be significantly higher than that of the KFe/CT/nylon fiber (16.9%) at an initial Cs+ concentration of 0.67 mg/L.